The Observability of Plasmoid-powered gamma-Ray Flares with the Fermi Large Area Telescope - Meyer, Manuel; Petropoulou, Maria; Christie, Ian M. (Astrophysical Journal, 2021)
The exact mechanism for the production of fast gamma-ray variability in blazars remains debated. Magnetic reconnection, in which plasmoids filled with relativistic particles and magnetic fields are formed, is a viable candidate to explain the broadband electromagnetic spectrum and variability of these objects. Using state-of-the-art magnetic reconnection simulations, we generate realistic gamma-ray light curves that would be observed with the Fermi Large Area Telescope. A comparison with observed gamma-ray flares from flat spectrum radio quasars (FSRQs) reveals that magnetic reconnection events lead to comparable flux levels and variability patterns, in particular, when the reconnection layer is slightly misaligned with the line of sight. Emission from fast plasmoids moving close to the line of sight could explain the fast variability on the timescales of minutes for which evidence has been found in observations of FSRQs. Our results motivate improvements in existing radiative transfer simulations as well as dedicated searches for fast variability as evidence for magnetic reconnection events.
CRIS-Team WoS Importer:2021-05-14